2015
DOI: 10.1186/s40517-014-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ambient seismic noise near a deep geothermal reservoir and implications for interferometric methods: a case study in northern Alsace, France

Abstract: Background: Ambient noise correlation techniques are of growing interest for imaging and monitoring deep geothermal reservoirs. They are simple to implement and can be performed continuously to follow the evolution of the reservoir at low cost. However, these methods rely on assumptions of spatial and temporal uniformity of seismic noise sources. Violating them can result in misinterpretation of seismic velocities owing to preferential noise propagation directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…The asymmetry between causal and acausal sides is also consistent in this period range. Higher amplitudes are observed on the causal side due to prominent microseismic sources located in the northern Atlantic Ocean for back azimuths approximately 290–310°N (Lehujeur et al, , ). For waveforms of both networks, we compare the ratio between the peak amplitude of direct arrivals (green time window, Figure ) and the root‐mean‐square of the NCF in the coda part (blue time window, Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The asymmetry between causal and acausal sides is also consistent in this period range. Higher amplitudes are observed on the causal side due to prominent microseismic sources located in the northern Atlantic Ocean for back azimuths approximately 290–310°N (Lehujeur et al, , ). For waveforms of both networks, we compare the ratio between the peak amplitude of direct arrivals (green time window, Figure ) and the root‐mean‐square of the NCF in the coda part (blue time window, Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…At Soultz‐sous‐Forêts, the potential of such techniques was first demonstrated by Calò et al () based on a 22‐station network. A comprehensive study of the properties of the ambient seismic noise recorded in the area has revealed a strong directivity of the ambient seismic noise at periods between 1 and 5 s that mainly originates from the Northern Atlantic Ocean and the Mediterranean Sea (Lehujeur et al, ). Such directivity patterns in the ambient seismic noise may affect the tomographic models obtained with sparse seismological networks (Lehujeur et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency band of interest is therefore not impacted by the onset of the well operations in July 2013. This allows us to rule out human activity as a source for the changes at periods above 1 s, an observation that is also confirmed by a detailed characterization of ambient noise near the geothermal sites in northern Alsace from Lehujeur et al [].…”
Section: Monitoring the St Gallen Project With Ambient Noise Correlamentioning
confidence: 99%
“…Second, the coda of the lapse crosscorrelations has proved less sensitive to temporal variations in the illumination pattern than the direct (first) arrival (e.g. Hadziioannou et al 2009;Colombi et al 2014;Lehujeur et al 2015). Reducing the sensitivity of lapse crosscorrelations to the illumination pattern is therefore of immediate interest for such studies.…”
Section: Temporal Stabilitymentioning
confidence: 99%